TEENAGERS' PERCEPTION TOWARD LANGUAGE USE IN PUBLIC PLACE ADVERTISEMENT - Dielma Triyuni; Fadhilla Fadhilla; Liska Widya Putri (Universitas Islam Sumatera Utara (UISU), 2018)
This study aimed to investigate the teenagers’ perception towards language use in advertisement. Advertisement is the best way to communicate to the customers. Advertisement helps informs the customers about the brands available in the market and the variety of products useful to them. Advertisement is for everybody including kids, young and old. It is done using various media types, with different techniques and methods most suited. Advertisements are of great importance for any business activity as it attracts people to use the particular service. Most of the businessmen are using various different means of communication to reach people around the world and turn them into leads that can be further turned into potent customers. Visual content and design in advertising have a very great impact on the consumer, but it is language that helps people to identify a product and remember it. The research is done by means of descriptive qualitative method supported by questionnaire in data collection procedures. The results show that the perceptions of teenagers towards advertisements are the language used is simple and easy to remember and advertisements functions as reminder.